Exploring the effect of different application rates of biochar on the accumulation of nutrients and growth of flue-cured tobacco (Nicotiana tabacum) - Yang, Yingfen; Ahmed, Waqar; Ye, Chenghu; Yang, Linyuan; Wu, Lianzhang; Dai, Zhenlin; Khan, Khalid Ali; Hu, Xiaodong; Zhu, Xiaohong; Zhao, Zhengxiong (Frontiers in Plant Science, 2024)
Background Biochar application has become one of the most potential tools to improve soil fertility and plant growth for sustainable and eco-friendly agriculture. However, both positive and negative effects of biochar application have been recorded on plant growth and soil fertility. Methods This study investigated the impact of different application rates (0, 600, 900, 1200, and 1800 kg/ha) of biochar on the soil nutrient contents, accumulation of nutrients and dry matter in different plant parts, and growth of flue-cured tobacco plants under field conditions. Results Results demonstrated that soil organic carbon pool and carbon/nitrogen ratio were increased proportionally with the increasing dosage of biochar, 25.54 g/kg and 14.07 g/kg compared with control 17 g/kg and 10.13 g/kg, respectively. The contents of soil total nitrogen were also significantly increased after biochar application in the middle (1.77 g/kg) and late-growth (1.54 g/kg) stages of flue-cured tobacco than in control (1.60 g/kg and 1.41 g/kg, respectively). The contents of soil nitrate nitrogen were also higher under low (600 and 900 kg/ha) application rates of biochar and reduced when higher (1200 and 1800 kg/ha) dosages of biochar were applied. However, it was observed that varying application rates of biochar had no impact on soil ammonium nitrogen content during the growth period of flue-cured tobacco plants. The nutrient accumulation (N, P, K) in different parts of flue-cured tobacco plants was significantly increased under a low application rate of biochar, which enhanced the soil and plant analyzer development values, effective leaves number, growth, dry matter accumulation, and leaf yield of flue-cured tobacco. In contrast, the high biochar application rate (1200 and 1800 kg/ha) negatively impacted nutrient accumulation and growth of flue-cured tobacco. Conclusion Conclusively, the optimum application of biochar (600 and 900 kg/ha) is beneficial for plant growth, soil fertility, accumulation of nutrients, and dry matter in different plant parts. However, excessive biochar application (> 900 kg/ha) could inhibit flue-cured tobacco plant growth. This study provides a theoretical foundation for biochar application in tobacco and other crop production to obtain agricultural sustainability and economic stability.